Factors associated with the competences of staff in Malaysian nursing homes - Nur A’mirah Mohd Yaziz; Nurul Ashykin Abd Aziz; Hasif Rafidee Hasbollah; Siti Nabilah Mohd Rosdi; Mohd Firdaus Mohd Nasir; Mohd Shafhuan Yusran (2015)
This paper aims to determine the factors associated to the competencies of staff in Nursing Homes Malaysia. A survey using self-administered questionnaires was conducted that involved 28 items. Pearson Chi-Square, test was applied in this study. The analysis proved that there is a relationship between the competencies of staff with all three factors, which are People, Programme, and Process. The most significant item for people is “the supervisor help in list the marketable skills of staff” (p-value<0.001, = 44.043). However, the analysis indicated that “supervisor inform potential organisational changes to the staff” do not have a significant relationship with competencies of staff for the people factor (p-value>0.05, = 16.793). All items under programme have significant relationship with the competencies of staff. Though, for the programme factor, it showed that items such as “training programme that depends on the Nursing Homes policy”; “ease the pressure of work to give chance in practising new skill”; and “staff who applied the training programme on job are given preference in managing Nursing Homes” have the most significant relationships with the competencies of staff (p-value<0.001, = 41.381, 37.589, 35.533). As for the process factor, all items have a significant relationship with competencies of staff. Therefore, all items in the process factor showed that “process is important to ensure the best quality services”; “process implemented for continuous improvement towards staff competencies”; “engagement in a continuous process”; and “the comprehensive staff competencies practice derive from a process” have the most significant relationship with competency level (p-value<0.001, = 28.774, 38.181, 41.067, 35.750). This study is an initial phase in developing a Theoretical Framework for Staff Competencies in Nursing Homes Malaysia.